New Polyfluorinated Cyanine Dyes for Selective NIR Staining of Mitochondria. Issue 34 (17th May 2019) - Braun, Alexander B.; Wehl, Ilona; Kölmel, Dominik K.; Schepers, Ute; Bräse, Stefan
Abstract: In this communication, the synthesis of three unknown polyfluorinated cyanine dyes and their application as selective markers for mitochondria are presented. By incorporating fluorous side chains into cyanine dyes, their remarkable photophysical properties were enhanced. To investigate their biological application, several different cell lines were incubated with the synthesized cyanine dyes. It was discovered that the presented dyes can be utilized for selective near‐infrared‐light (NIR) staining of mitochondria, with very low cytotoxicity determined by MTT assay. This is the first time that polyfluorinated cyanine fluorophores are presented as selective markers for mitochondria. Due to the versatile applications of polyfluorinated fluorophores in bioimaging and materials science, it is expected that the presented fluorophores will be stimulating for the scientific community. Abstract : Selective staining : Three new polyfluorinated cyanine dyes were developed and their application as selective markers for mitochondria in several different cell lines is shown. The presented cyanine dyes can be utilized for selective near‐infrared‐light (NIR) staining of mitochondria, with very low cytotoxicity as determined by MTT assay.